Significant coercivity enhancement of hot deformed NdFeB magnets by doping Ce-containing (PrNdCe)70Cu30 alloys powders. (15th March 2018) - Chang, H.W.; Lee, Y.I.; Liao, P.H.; Chang, W.C.
Abstract: Coercivity enhancement of hot-deformed NdFeB magnets made from commercially available NdFeB powders doped with Ce-containing alloys is demonstrated. By doping (Pr71 Nd27 Ce2 )70 Cu30 powders, where Pr71 Nd27 Ce2 is a commercial mischmetal, the hot-deformed magnets exhibit significant enhancement of coercivity from 15.0 kOe to 19.0 kOe, and it can reach 20.1 kOe by doping higher Ce-content (Pr71 Nd9 Ce20 )70 Cu30 powders, yet sustains high energy product. The magnetic isolation effect with Ce-containing phase in the grain boundary and the microstructure refinement lead to coercivity enhancement. This study provides an economic way to enhance coercivity of hot deformed NdFeB magnets without using heavy rare earth. Graphical abstract: Image 1